1999
DOI: 10.1038/sj.ki.4490857
|View full text |Cite
|
Sign up to set email alerts
|

Anemia and carnitine supplementation in hemodialyzed patients

Abstract: identify those HD patients who might have a benefit of carni-Anemia and carnitine supplementation in hemodialyzed patine supplementation, as well as studies concerning the optimal tients. Carnitine supplementation in hemodialyzed patients was dosage, duration, and way of administration of carnitine supstudied in a double-blinded, randomized, controlled trial in plementation and its mechanism of action, are required. order to elucidate the effect of intravenous carnitine on renal anemia in patients treated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
48
0
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 47 publications
2
48
0
3
Order By: Relevance
“…In a recent meta-analysis study on the effects of intravenous L-carnitine treatment in adult patients on maintenance HD [4], five of the six randomized trials reviewed showed reduction of the required rhEPO dose for maintaining a certain target hemoglobin concentration in both carnitine and control groups. Moreover, the rhEPO resistance index, as defined by the rhEPO dose given per gram of hemoglobin to maintain a constant hemoglobin level [17], was reported to improve in carnitine-treated patients in three out of four studies [4]. At the same time, the studies did not demonstrate that L-carnitine supplementation had an effect on serum lipid profile, myocardial function, or exercise capacity [4].…”
Section: Discussionmentioning
confidence: 97%
“…In a recent meta-analysis study on the effects of intravenous L-carnitine treatment in adult patients on maintenance HD [4], five of the six randomized trials reviewed showed reduction of the required rhEPO dose for maintaining a certain target hemoglobin concentration in both carnitine and control groups. Moreover, the rhEPO resistance index, as defined by the rhEPO dose given per gram of hemoglobin to maintain a constant hemoglobin level [17], was reported to improve in carnitine-treated patients in three out of four studies [4]. At the same time, the studies did not demonstrate that L-carnitine supplementation had an effect on serum lipid profile, myocardial function, or exercise capacity [4].…”
Section: Discussionmentioning
confidence: 97%
“…[23] Hurot et al [25] established that L-carnitine improves anemia in uremic patients before routine administration of the rHuEPO in the treatment of the anemia. [23] Hurot et al [25] established that L-carnitine improves anemia in uremic patients before routine administration of the rHuEPO in the treatment of the anemia.…”
Section: Discussionmentioning
confidence: 99%
“…In the placebo‐controlled double‐blind trial by Labonia (6), it is specifically stated that all patients were on dialysis at least 1 year and had normal iron, folate, and vitamin B 12 status, as well as an absence of severe hyperparathyroidism. In the randomized trial by Kletzmayr et al (5), the mean PTH level was specifically noted as slightly elevated compared with target goals for all patients, and intravenous iron therapy was uniform for both the carnitine‐ and placebo‐treated groups. Moreover, in the randomized trial by Caruso et al (4) on the effect of carnitine in elderly dialysis patients, all subjects had normal iron status, PTH levels less than 150 pg/ml, and no clinical evidence of aluminum intoxication.…”
mentioning
confidence: 95%
“…(4) documented a significant reduction in EPO use among elderly dialysis patients treated with L‐carnitine injection, the majority of studies of L‐carnitine and EPO, including those of Kletzmayr et al. (5) and Labonia (6), were performed in the more general dialysis population. Furthermore, control of iron and PTH status was specifically incorporated in all three of these trials.…”
mentioning
confidence: 99%